2022
DOI: 10.1101/2022.12.13.22283439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unbiased serology reveals autoimmunity and HIV antibody signatures in HIV CNS Escape

Abstract: Background: Antiretroviral therapy (ART) suppresses plasma and cerebrospinal fluid (CSF) HIV replication with occasional asymptomatic episodes of detectable HIV RNA known as asymptomatic (AS) escape. Neurosymptomatic (NS) CSF escape is a rare exception in which CNS HIV replication occurs in the setting of neurologic impairment. The origins of NS escape are not fully understood. Methods: Using a large cohort of PLWH (n=111), including elite controllers (n=4), viral controllers (n=4), ART untreated subjects (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Here, we report for the first time AnkG autoantibodies in the CSF of two patients with neurological illness. Because case 1 is living with HIV, we verified that AnkG autoantibodies were not secondary to his HIV status ( 8 ). Albeit extremely rare, these data suggest that, like myriad other antibodies targeting the AIS and NoR, AnkG autoantibodies are biomarkers of neurological autoimmunity.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Here, we report for the first time AnkG autoantibodies in the CSF of two patients with neurological illness. Because case 1 is living with HIV, we verified that AnkG autoantibodies were not secondary to his HIV status ( 8 ). Albeit extremely rare, these data suggest that, like myriad other antibodies targeting the AIS and NoR, AnkG autoantibodies are biomarkers of neurological autoimmunity.…”
Section: Discussionmentioning
confidence: 82%
“…Case 1 CSF IgG colocalized with AnkG at the AIS and NoR, thereby confirming AIS-NoR immunoreactivity ( Figure 2B ). A review of TBIF results from a separate study revealed that none of 46 CSF samples from people living with HIV produced AIS/NoR immunostaining ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation